Estudo da cinética de secagem e extração de compostos bioativos presentes em Egletes viscosa Less (macela-da-terra) - Martins, Camila Mota (2018)
Egletes viscosa (Asteraceae), herbaceous popularly known as "macela-da-terra", is used by the brazilian traditional medicine due to the therapeutic properties of its flower buds, which contain ternatin (1), hawtriwaic acid lactone (2) and centipedic acid (3) as active principles. The objective of the present study was to determine the best processing conditions to obtain these substances. In this context, a study of kinetic drying and extraction with pressurized liquid solvent (PLE) was made. The drying was carried out in a circulation and air renovation oven with three temperatures (50, 60 and 70 ° C), presenting a final moisture content of 16.5% in flower buds. The experimental drying curve showed only a period of humidity drop and time reduction with the increase of the tested temperatures. The dry material was extracted by water infusion, which is the form popularly used for medicinal purposes, and the tea compounds were quantified by UPLC/QDA-SIM. There was no significant difference (p ≤ 0.05) between the concentrations of the bioactive compounds at the different tested temperatures, showing that the flower buds can be dried at high temperatures (70 ° C) without changing their quality. The drying model generated from the Fick’s second law presented effective moisture diffusivity (Deff) between 5.55 x 10-9 and 1.72 x 10-9 m2 / s and activation energy of 45.14 KJ / mol. Although the model is simplistic for the complex structure of the material surface, it was considered satisfactory. For the extraction experiments, preliminary tests were carried out, which showed the efficiency of the PLE and the solvent ethanol. Then, the extraction’s optimization was done from an experimental design of the central composite type, having as independent variables temperature (70-130 °C) and proportion of solvent ethanol/water (20-80 %). The results of the extractions showed that the temperature, the extraction time and the proportion of the ethanol/water solvents were significant for the extraction of the compounds (1-3). The best operational condition obtained with the optimization of the extraction by PLE was with 92.4 % ethanol, 100 °C, one cycle and 15 min of extraction. The extraction by PLE seemed to be promising, opening the possibility to establish operational parameters for a maximum extraction of the interest compounds, with the exception of the ternatin that reached the highest concentration in Soxhlet extraction